2017
DOI: 10.1007/s11356-017-9786-7
|View full text |Cite
|
Sign up to set email alerts
|

Ozone risk assessment in three oak species as affected by soil water availability

Abstract: To derive ozone (O) dose-response relationships for three European oak species (Quercus ilex, Quercus pubescens, and Quercus robur) under a range of soil water availability, an experiment was carried out with 2-year-old potted seedlings exposed to three levels of water availability in the soil and three levels of O pollution for one growing season in an ozone free-air controlled exposure (FACE) facility. Total biomass losses were estimated relative to a hypothetical clean air at the pre-industrial age, i.e., a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…Hoshika et al (2017a) tested a ratio of photosynthesis to ozone uptake as an index for the assessment of foliar visible injury in Oxford poplar. The same team (Hoshika et al 2017b) investigated in a free-air controlled exposure facility the ozone doseresponse relationships for three European oak species under a range of soil water availability. Physiological and biochemical responses to long-term exposure to ozone of two Italian provenances of Fraxinus excelsior were the focus of the paper presented by Cotrozzi et al (2017a).…”
mentioning
confidence: 99%
“…Hoshika et al (2017a) tested a ratio of photosynthesis to ozone uptake as an index for the assessment of foliar visible injury in Oxford poplar. The same team (Hoshika et al 2017b) investigated in a free-air controlled exposure facility the ozone doseresponse relationships for three European oak species under a range of soil water availability. Physiological and biochemical responses to long-term exposure to ozone of two Italian provenances of Fraxinus excelsior were the focus of the paper presented by Cotrozzi et al (2017a).…”
mentioning
confidence: 99%
“…On a long-term basis, ambient O 3 has been considered as a stress factor contributing to impairment of forest health status and its influence has been studied from different aspects. In spite of clear evidence of O 3 harmful effects observed in laboratory experiments, fumigation chambers, or FO 3 X (Free air O 3 eXposure) experiments (Sandermann et al, 1997;Paoletti et al, 2017;Franz et al, 2018;Hoshika et al, 2018), the field evidence for impacts of O 3 exposure on tree growth is not that clear (De Vries et al, 2014;Cailleret et al, 2018). Moreover, observations in real stand conditions from numerous regions show that measured high O 3 exposures or modeled high O 3 stomatal flux do not correspond with unclear impacts on forest ecosystems (e.g., Ferretti et al, 2007;Matyssek et al, 2007;Waldner et al, 2007;Baumgarten et al, 2009).…”
Section: Relevance Of Our Results To Forestsmentioning
confidence: 99%
“…In fact, several studies (McLaughlin et al 2007;Sun et al 2012) reported substantial increases of transpiration at the ecosystem-level in southeastern US forests that were attributed to ozone-induced stomatal sluggishness. This exacerbates the effect of drought because impaired stomata reduce the ability of trees to conserve water (Hoshika et al 2018a). In the Aspen FACE experiment, the stomatal CO 2 response of aspen-birch communities was inhibited by ozone and this effect developed progressively over the growing season (Onandia et al 2011).…”
Section: Model Descriptionmentioning
confidence: 99%
“…As a result, ozone decreases intrinsic water use efficiency and thus increases C i (e.g., Farage and Long 1995). Using empirical measures of stomatal response to ozone and water stress in a different free-air ozone exposure experiment (Hoshika et al 2018a; see Paoletti et al 2017 for the detail of the experiment), we developed equations to modify C i (Cimodifier) as a function of cumulative ozone dose, water stress and species susceptibility to stomatal sluggishness in response to ozone, to reflect the effects of ozone on stomatal conductance:…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation